2014
DOI: 10.3233/jad-140852
|View full text |Cite
|
Sign up to set email alerts
|

Combining Select Neuropsychological Assessment with Blood-Based Biomarkers to Detect Mild Alzheimer's Disease: A Molecular Neuropsychology Approach

Abstract: Background The current project sought to create combined biomarker-cognitive profile to detect mild Alzheimer’s disease. Methods Data was analyzed from 266 participants (129 AD cases [Early AD n=93; Very Early AD n=36]; 137 controls) enrolled in the Texas Alzheimer’s Research and Care Consortium (TARCC). Non-fasting serum samples were collected from each participant and assayed via a multi-plex biomarker assay platform using electrochmiluminescence (ECL). Logistic Regression was utilized to detect early AD u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Systemic infection in AD was also associated with a reduction in several pro-inflammatory cytokines, mainly associated with the adaptive immune system. The few studies that have examined their role in AD have found: (i) elevated serum IL7 in early to mild AD [ 20 ]; (ii) elevated IL12p40 levels in the cerebrospinal fluid (CSF) of Alzheimer’s patients [ 68 ]; (iii) administration of IL12p40 subunit blocker enhanced microglial phagocytosis and reduced inflammation in Aβ transgenic mice [ 68 ]; (iv) raised IL15 levels in the CSF and serum of Alzheimer’s patients correlated with severity of cognitive dysfunction [ 6 , 58 ]; (v) increased peripheral IL16 in AD [ 19 ]; and overexpression of IL17A decreased soluble Aβ levels without exacerbating neuroinflammation in a mouse model of Aβ accumulation [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic infection in AD was also associated with a reduction in several pro-inflammatory cytokines, mainly associated with the adaptive immune system. The few studies that have examined their role in AD have found: (i) elevated serum IL7 in early to mild AD [ 20 ]; (ii) elevated IL12p40 levels in the cerebrospinal fluid (CSF) of Alzheimer’s patients [ 68 ]; (iii) administration of IL12p40 subunit blocker enhanced microglial phagocytosis and reduced inflammation in Aβ transgenic mice [ 68 ]; (iv) raised IL15 levels in the CSF and serum of Alzheimer’s patients correlated with severity of cognitive dysfunction [ 6 , 58 ]; (v) increased peripheral IL16 in AD [ 19 ]; and overexpression of IL17A decreased soluble Aβ levels without exacerbating neuroinflammation in a mouse model of Aβ accumulation [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through this work, researchers have sought to provide utility for identifying blood-based biomarkers associated with neuropsychological functioning to establish biomarker profiles of disease states [7] . This effort termed Molecular Neuropsychology has identified biomarker profiles of neurocognitive functioning and begun combining select blood biomarkers with select cognitive assessments with the goal of establishing a point-of-care device for primary care settings that can be used to identify those with early AD [7] , [8] . This work has stemmed from the growing need for a rapid screening measure for those early in the disease process.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent work, we demonstrated that combining two of the top five biomarkers (TNF-α and IL-7) with one neuropsychological measure (Clock 4-point), yielded excellent accuracy in detecting early AD [8] . Even for very early AD cases, this approach was able to provide an overall accuracy of 91% with a sensitivity of 97% and specificity of 72% [8] . This work has shown that combining neuropsychological screening measures with a limited number of biomarkers can increase the ability to identify those who are at a higher risk for the development of AD.…”
Section: Introductionmentioning
confidence: 99%
“…The longitudinal dynamics and predictive performance of this multimodal approach is not definitely established and should be examined according to our expectation, in terms of sensitivity and/or specificity, and their condition, i.e. in combination or isolated (166, 167). Moreover, opinions of regulatory agencies and industry stakeholders in AD biomarker discovery area are constantly in discussion and development (168170).…”
Section: Directions For Ad Biomarker Researchmentioning
confidence: 99%